Genealogical Myth of the Buryats of the Hori Tribe: Calendar and Ritual - N. B. Dashieva (Научный диалог)
The plot of the genealogical myth of the Buryats of the Khori tribe is studied in the article as a historical and cultural source reflecting ideological attitudes, which were also a historical fact. It has been established that the myth about the origin of the Khori-Buryats is the plot of the areal cosmogonic myth. It is stated that the historical-genetic and cultural-semantic interpretation of the main events of the myth, when identified with information from archaeological, historical, ethnographic, folklore and linguistic sources, makes it possible to see in the plot of the myth the cult of the sun, the type of calendar of the solar year caused by it and the model of calendar rites of the early nomads of the steppes of Central Asia. It was revealed that the plot of the myth came to the northern shore of Lake Baikal with the carriers of the culture of tiled graves — the ethnic ancestors of the Turkic-Mongol peoples with Indo-Iranian cosmological ideas expressed in the calendar, calendar holidays, calendar rituals and calendar culture in general. It is proved that the main events of the myth are reflected in the rock paintings of the Sagan-Zaba Bay on the northern coast of Lake Baikal. It is shown that the plot of the genealogical myth of the Khori-Buryats acts as a text of culture, which is a means of preserving information about the picture of the world, which in the traditional culture of the tribe was controlled by a rite. It is noted that the historical and cultural origins of the myth go back to the archaeological Scythian-Siberian culture of the Iron Age (VI—III centuries BC).